HADHĀNAH BAGI SUAMI AKIBAT ISTRI MURTAD PERSPEKTIF KAIDAH DAR’ MAFĀSID : STUDI ANALISIS PUTUSAN - Al Awshat, Muhammad Ali; Abd. Rouf (Indonesian Journal of Shariah and Justice, 2025)
Inthe. case. ofcustody(hadhanah)due. toapostate. wife.,the.re. are. twoconflictinginte.re.sts.On the. one. hand, childre.n ne.e.d close.ne.ss to the.ir mothe.r as the. main figure. in the.ir upbringing since. childhood.Howe.ve.r,onthe. othe.rhand,the.re. isaconce.rnthatifthe. childiscare.dforby a mothe.r who has apostatize.d, he.r faith and re.ligious unde.rstanding may be. affe.cte.d. This cre.ate.s a dile.mma be.twe.e.n maintaining the. child's e.motional bond with his mothe.r and maintaining his re.ligious be.lie.fs and e.ducation. One. of the. fiqh rule.s that is re.le.vant in this conte.xt is dar' al-mafāsid muqaddam a'lā jalb al-mashālih, which state.s that re.je.cting harm must take. pre.ce.de.nce. ove.r achie.ving be.ne.fit. This study aims to analyze. the. judge.'s conside.ration in de.te.rmining child custody in divorce. case.s due. to apostate. wive.s in the. Re.ligiousCourt.Withnormative. juridicalme.thodandcase. approach.The. re.sultsshowe.dthat the. judge. re.fe.rre.dtothe. opinionsofthe. Shafi'iyyahandHanafiyyahscholars,whoe.mphasize.d that child custody must be. give.n to Muslim pare.nts. Base.d on the. rule. of dar' al-mafāsid muqaddam a'lā jalb al-mashālih, the. judge. de.cide.d to give. custody to the. fathe.r to maintain the. child's faith and re.ligious e.ducation.